The Relationship Between Breakfast Habits with Nutritional Status And Study Achievement of SMA Negeri 17 Medan Students (Nutrizione: Nutrition Research And Development Journal, 2023)
Teenagers are the age that are prepared to become human resources who will continue development in Indonesia. The purpose of this study was to determine the relationship between breakfast habits and nutritional status and academic achievement of SMA Negeri 17 Medan students. This type of research is descriptive analytic with cross-sectional design. The population in this study were students of SMA Negeri 17 Medan. The sample in this study was taken using a proportional stratified random sampling technique on 100 students of SMA Negeri 17 Medan. Data collection on breakfast habits was carried out using an instrument in the form of a questionnaire. Nutritional status data was taken by measuring the respondent's weight and height, which then calculated nutritional status based on BMI/U. Meanwhile, learning achievement data was obtained using the average value of students' last semester report cards. Data analysis used the Chi Square test. The results showed that there was a significant relationship between breakfast habits and nutritional status (p=0.022) and there was a significant relationship between breakfast habits and student achievement (p=0.007). However, there was no significant relationship between nutritional status and student achievement (p=0.209). It can be concluded that there is a relationship between breakfast habits and nutritional status and student achievement of SMA Negeri 17 Medan.